OPTIMALISASI PENILAIAN AFEKTIF DALAM PEMBELAJARAN SKI : MENDUKUNG PENGEMBANGAN SIKAP - Nadhifa Nur Alifazahro; Tri Putri Siti Fatimah; Aulia Nur Rachmah (JIP: Jurnal Ilmu Pendidikan, 2024)
Not only does it provide knowledge, but religious education should also provide a change that can shape an attitude, a personality, and a skill. In education, of course, one must carry out an evaluation to be a parameter of validity of something that has been planned and also that has already been arranged, especially evaluation in the affective sphere, because back again with the statement that religious education should not only be able to provide a religious science but also can influence attitudes, By using qualitative research methods and then presenting the research results in a descriptive way, the results of our observations and interviews show that each subject has a learning plan that contains all the learning strings from beginning to end and also the learning evaluation of the subject. Evaluation of affective learning areas in Islamic Cultural History subjects using honest self-assessment and also peer judgment using a lift and pupils filling each other's lift of my peer. From this evaluation, the teacher of the subject can evaluate the attitude of the student other than by observing the student's attitude when learning is taking place in the classroom.